2018
DOI: 10.1101/275917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study meta-analysis of the Alcohol Use Disorder Identification Test (AUDIT) in two population-based cohorts (N=141,932)

Abstract: words]Alcohol use disorders (AUD) are common conditions that have enormous social and economic consequences. We obtained quantitative measures using the Alcohol Use Disorder Identification Test (AUDIT) from two population-based cohorts of European ancestry: UK Biobank (UKB; N=121,604) and 23andMe (N=20,328) and performed a genome-wide association study (GWAS) meta-analysis. We also performed GWAS for AUDIT items 1-3, which focus on consumption (AUDIT-C), and for items 4-10, which focus on the problematic conse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…Broad sense heritability estimates of 25-61% for alcohol consumption have previously been reported from studies of twins 1, 2, 5 . The SNP effects for alcohol consumption were estimated at 6%, which again are lower than, but closer to, estimates reported in the UK Biobank for alcohol consumption (13%) and AUDIT scores in the 23andMe sample (12%) 28,36 . Previous studies have suggested that genetic interactions and improper modeling of the environment can inflate heritability estimates 37,38 .…”
Section: Discussionsupporting
confidence: 45%
“…Broad sense heritability estimates of 25-61% for alcohol consumption have previously been reported from studies of twins 1, 2, 5 . The SNP effects for alcohol consumption were estimated at 6%, which again are lower than, but closer to, estimates reported in the UK Biobank for alcohol consumption (13%) and AUDIT scores in the 23andMe sample (12%) 28,36 . Previous studies have suggested that genetic interactions and improper modeling of the environment can inflate heritability estimates 37,38 .…”
Section: Discussionsupporting
confidence: 45%
“…Summary-level data of large GWAS were obtained for ADHD (clinically diagnosed versus controls, n=55,374 4 ), smoking (initiation (ever regularly smoked or ≥100 cigarettes during lifetime), n=1,232,091; cigarettes per day, n=337,334; cessation (former versus current smokers), n=547,219 17 ; lifetime smoking, n=463,003 35 ), alcohol use (drinks per week, n=941,280 17 ; alcohol problems (AUDIT total score: Alcohol Use Disorders Identification Test), n=121,604 19 ; alcohol dependence (clinically diagnosed versus controls), n=46,568 36 ), cannabis use (initiation (ever used during lifetime), n=162,082 16 ) and coffee consumption (cups per day, n=91,462 18 ). When smoking initiation, cigarettes per day, smoking cessation or alcohol drinks per week was the outcome in the MR analysis, data of one of the included cohorts, 23andMe, were not available, resulting in sample sizes of n=632,783, n=263,954, n=312,821 and n= 537,341, respectively.…”
Section: Datamentioning
confidence: 99%
“…Family studies have shown that ADHD and substance use are moderately to highly heritable, and indicate shared genetic risk factors 14,15 . Overlap in genetic risk has also been examined in recent genome-wide association studies (GWAS) of ADHD and substance use 4,[16][17][18][19] . Substantial genetic correlations were found for ADHD with ever versus never smoking (rg=0.…”
Section: Introductionmentioning
confidence: 99%
“…the relative proportion of one's diet derived from fat, carbohydrate and protein), it was reported that FGF21, a predominantly liver-derived hormone, suppresses intake of simple sugars and alcohol in mice and consumption of the artificial sweetener saccharin in primates (Talukdar et al 2016;von Holstein-Rathlou et al 2016). Since then, these findings have been replicated and generalized in mice and humans (Evangelou et al 2018;Frayling et al 2018;Meddens et al 2018;Sanchez-Roige et al 2018).…”
Section: Introductionmentioning
confidence: 96%